Boom & Bust. Local strategy for big events. A community survival guide to turbulent times - Kristof Van Assche; Leith Deacon; Monica Gruezmacher; Robert Summers; Stephane Lavoie; Kevin Jones; Michael Granzow; Lars Hallstrom; John Parkins (InPlanning and University of Alberta, Faculty of Extension, 2017)
Boom and Bust: Local strategy for big events is the result of a collective effort at the University of Alberta to better understand the dramatic ups and downs which too often characterize western Canadian communities. From the Canadian analysis stems this book, which can be helpful in any community experiencing radical ups and downs, any community worried about its future. It offers community leaders, politicians, administrators, academics, students, and all active citizens helpful techniques to analyze the current state of their own community, understand how it got where it is today, and ultimately, identify possible ways forward. We encourage analysis of historical paths and policy contexts to better understand what strategies might work (or not) in a community. The authors encourage readers to learn from local histories, a broad range of tested theories, and the experiences of other communities to develop a context-sensitive strategy of asset building, while at the same time taking on an informed understanding of what assets and resources could support long-term development planning for their communities. They demonstrate that assets become such within a context and within a narrative, forming a story about the past, present, and future of the community. By showing the importance of reinvention and the dangers of rigid identity, the authors call on communities to re-evaluate their assets and their dependencies, and ultimately to reintroduce long-term perspectives within governance.
Keywords: P11; O21; O31; O43; 330; local strategy; community development; public management; governance; sustainability; long term strategy; economic development; planning